An Investigation on the Adaptive Modal Combination Procedure for Seismic Evaluation of Buildings Considered Soil Structure Interaction - Hong-An Nguyen; Chatpan Chintanapakdee (Institut Teknologi Sepuluh Nopember, 2017)
Nonlinear response history analysis (NL-RHA) is a powerful tool for seismic analysis of structures. The seismic performance of structures can be estimated accurately due to a set of ground motions. However, NL-RHA is an onerous task to estimate seismic demands due to its complexity for practical design applications. Therefore, nonlinear static procedures (NSPs), which are rooted in structural dynamic theory, are developed as an alternative to rigorous NL-RHA. NSPs are now widely used in engineering practice to evaluate seismic responses of structure in the inelastic range. The main objective of this study is to assess the bias and accuracy of the adaptive modal combination (AMC) procedure, which is modified from the modal pushover analysis (MPA) procedure, for seismic evaluation of buildings. Three-, 9-, 18-storey buildings were analyzed due to two sets of strong ground motions having 2% and 10% probability of being exceeded in 50 years. The influence of soil-structure interaction in the analysis was also considered by using Beam-on-Nonlinear-Winkler-Foundation modeling. The assessment is based on comparing seismic displacement demands such as target roof displacements, peak floor displacements and inter-storey drifts. The AMC estimates are compared to results from nonlinear response history analysis (NL-RHA) and results from AMC procedure considered only first mode (AMC- 1st mode). The obtained results show that the AMC procedure provides reasonably accurate results in estimating seismic demands of studied buildings.